Effect of Endophytic Fungi on the Growth of Sengon (Falcataria moluccana) - Yunik Istikorini; Ahmad Faqih; Noor Farikhah Haneda; Ulfah Juniarti Siregar; Dimas Andrianto (Jurnal Sylva Lestari, 2022)
Endophytic fungi have been reported to promote plant growth and resistance to biotic and abiotic stresses. This study aimed to determine the effect of endophytic fungi application isolated from the sengon (Falcataria moluccana) seeds on the growth of sengon. The seed-borne endophytic fungi were applied when the session was three weeks old by sprinkling each suspension of endophytic fungi (103 to 106 spores/ml) on the soil around the plant roots. The experimental parameters evaluated were height, diameter, and total wet and dry weight. This study showed that endophytic fungi treatment has no significant effect on the stem diameter, total wet weight, and water content; but significantly affected the height and total dry weight. Cladophialophora sp. and Ascotricha sp. fungi increased the height growth of sengon, while Aspergillus sp. fungi increased the total dry weight against the control. Ochroconis sp. treatment was not significantly different from the control. The shoot-root ratio values range from 1.13-1.43, indicating that the seeds already have roots supporting plant growth. The Dickson quality index range from 0.65-1.03 suggested that the seedlings have good biomass distribution. Consequently, endophytic fungi have the potential to increase the growth of sengon seedlings. Keywords: endophytic fungi, Falcataria moluccana, seedling growth, sengon